THE INFLUENCE OF DIGITAL COMICS ON STUDENTS’ LEARNING OUTCOMES - Reka Aprianti; Akhbar, M Taheri; Selegi, Susanti Faipri (SEMESTA: Journal of Science Education and Teaching, 2024)
This study aims to determine whether or not there is an influence of digital comics on the science learning outcomes of fifth grade elementary school students on single substance and mixed substance material. The research method used was quantitative with true experimental and was designed using a Pretest-Posttest Control Group Design research design. The sample size for the research was 58 students who were divided into 2 groups, namely class V.A, which had 29 students as the experimental class and class V.B, which had 29 students as the control class. levence statistics, hypothesis testing using the t-test stated that both classes showed an rcount7.588 >ttable 1.672and the sig (2-tailed) value shows 0.000 < 0,05of  So it can be concluded that Ha is accepted. Based on this research data, it can be proven that there is an influence of digital comics on the science learning outcomes of fifth grade elementary school students in single substance and mixed substance materials.